The course of experimental giardiasis in Mongolian gerbil - Pecková, Radka; Sak, Bohumil; Květoňová, Dana; Kváč, Martin; Koriťáková, Eva; Foitová, Ivona (Parasitology research, 2018)
Fifteen Mongolian gerbils were inoculated with 10 × 106 viable trophozoites of Giardia intestinalis. Their faeces were examined daily by flotation method and the number of shed cysts was counted. Two animals (male and female) were euthanised at 4- to 5-day intervals (9, 14, 18 days post-infection (DPI)). The remaining nine gerbils were sacrificed and dissected at the end of the experiment (23 DPI). Their small intestinal tissues were processed for examination using histological sectioning and scanning electron microscopy and their complete blood count (CBC) was examined. The highest number of trophozoites at the total was observed in the duodenum in gerbils sacrificed on 14 DPI. Number of shed cysts was positively correlated with number of trophozoites rinsed from the intestine. Infected gerbils had lower body weight gain in comparison with control group and in three male gerbils; diarrhoea occurred during infection. Cyst shedding was negatively correlated with values of mean corpuscular haemoglobin concentration. Females showed another pattern in cyst shedding than males. This information needs to be taken into account while planning the experiments.
Keywords: Feces; Microscopy, Electron, Scanning; Gerbillinae; mikroskopie elektronová rastrovací; Gerbil model; Disease Models, Animal; mužské pohlaví; Giardia intestinalis; Giardia lamblia; duodenum; Giardiasis; Duodenum; modely nemocí na zvířatech; ženské pohlaví; zvířata; feces; Humans; Giardial intestinal distribution; Trophozoites; giardiáza; Female; trofozoiti; lidé; Male; Animals